Pareceristas ad hoc 2011 - admin, admin (Outros Tempos: Pesquisa em Foco - História, 2011)
Alan Kardec Gomes Pachêco Filho (UEMA) Andrea Pessanha (UFF-UNIABEU) André Roberto de Arruda Machado (UNIFESP) Agostinho Júnior Holanda Coe (UFPI – Picos) Cláudia Cristina Azeredo Atallah (USS) Claudio de Paulo Honorato (UFF) Claudio Furtado (UNICV) Carlos Benedito Rodrigues da Silva (UFMA) Denise Demetrio (UFF) Fernanda Thomas (UERJ) Gabriel Aladren (UFRJ) Helidacy Maria Muniz Corrêa (UEMA) Joana Bahia (UERJ) Lígio Maia (UFRN) Márcia Milena Galdez Ferreira (UEMA) Orlando Santos (UFBA) Paulo Henrique Silva Pacheco (UERJ-FEUDUC) Protásio Paulo Langer (UFGD) Reinaldo dos Santos Barroso Junior (UEMA/Darcy Ribeiro) Valdinéa Sacramento (UFBA) Valtéria Alvarenga (UESPI) Viviane de Oliveira Barbosa (UFMA) Yuri Costa (UEMA) REVISÃO Abílio Ângelo da Costa Neto